INTERDISCIPLINARY INTEGRATION ON THE BASIS OF THE GEOMETRICAL CONSTITUENT OF THE NATURAL SCIENTIFIC PICTURE OF THE WORLD - Ermak, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Fragmentariness of the picture of the world in majority modern students is a significant obstacle in the development of their scientific worldview. The lack of integrity of the image of the universe is aggravated by the prevalence of the clip-on thinking among students, which prevents the students from fully acquiring fundamental classical education. The formation of an integral scientific picture of the world is necessary for the realization of an in-dependent productive research activity. In whatever field this activity is carried out, it is closely related to the creation of spatial representations and the mental manipulation of them in the process of solving various problems. Spatial representations are ordered in the mind of the learner on the basis of the geometric component of the natural science picture of the world. Integrated content courses such as "Introduction to the Modern Geometry of the Universe" while teaching of students should be combined with the implementation of the principle of interdisciplinary integration in the development of the educational program, carried out on the basis of the geometric component of the natural-science picture of the world.